Culture Shocks at Japanese Workplace of Indonesian Student Taking Internship Program in Japan - Haryanti, P (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
The purpose of this study is to find out various aspects of culture shock experienced by Indonesian student taking internship in Japan especially at their workplace. The data were collected from 12 respondens by questioners and semi-structured interviewed via social media such as whatsApp, Messenger with Indonesian students who had taken internship program in Japan. One of the major findings of this study is those Indonesian student experienced cultural shock related to language, communication, relationship, values and norms at their workplace, appearances, beliefs and religion, but most of respondents felt confused and uncomfortable with language problems and the norms and values at the workplace. The problems faced by student interns related to language: 1) The Using of honorifics; 2) Terms related to work; 3) Kanji/Chinese Character that used for kinds of drink or food names. In related to norms and values at workplace, respondents had difficulty in understanding Japanese culture called tatemae and honne, hadaka no tsuki ai/nude communication, drinking habit, etc. Another culture shocks they experience related to appearance, dress they wear at work and also the concept of religion’s role to individual life. Finding the effect of Culture shock to the work performance is recommended for the next research.